Assessment of the Impact of the Rotavirus Vaccine Against Severe Rotaviral Diarrhea in Uzbekistan - Erkin Musabaev; Umed Ismailov; Nargiz Ibadullaeva; Aziza Khikmatullaeva; Ilham Norbaev; Umar Primov; Dilorom Ahrarova; Saidkhon Sharapov; Ulugbek Yusupov; Renat Latipov (Springer, 2023)
Abstract Background This article presents the results of a long-term study of the impact of rotavirus vaccination in Uzbekistan. Uzbekistan is the first country in the Central Asian region to introduce rotavirus vaccination into the national compulsory vaccination calendar. The study aimed to evaluate the impact of rotavirus vaccination on hospitalizations due to all-cause AGE and RVGE in children < 5 years of age in Uzbekistan. Methods Detection of rotavirus antigen was performed using Rotavirus-Antigen-IFA-BEST "Vector Best" kit (Novosibirsk, Russia). Results The total of 20,128 children under 5 years of age were hospitalized in sentinel hospitals with a diagnosis of acute gastroenteritis during the study period (2019-2020). Of this number of children, 4481 children (22.2%) were included in the study. Of 4481 children, 367 (8.2%) children tested positive for rotavirus. In our study, decrease in the rotavirus rate was noted in all age groups. The peak of rotavirus positivity occurred in the months of January and February. Conclusion The average rotavirus-positive rate in the period (2019-2020) was 8.2% and the absolute percentage decrease was 18.1% compared to the pre-vaccination period (2005-2009) where the rotavirus-positive rate was 26.3%. The percentage of prevented cases averaged 68.8%.